The Standard Metre: Has It Anything to Do With The Contingent A Priori - mohammad saeed mehr (حکمت و فلسفه, 2006)
kripke bas proposed a number of counteretxamples to the classic thesis, which ays that the class of necmary fropositions roincidn with the cla1ss of a priori ones. These counteretxamples involve some necessary a posten'ori trutbs as well as contingent a priori ones. Om cfbis exmnplu far the loller is the 1ta11dard metre example. In thi1 paper, after presenting a brief sketch of Kripke'1 proposal, I'll exan,ine the main ohjution1 to it and argue !hat all of them co,t!d be replied to. At the end, ho,vever,argue that the standard metre example enjoy1 much Im philosopbical significance than it appears to,and,considering the sprit,it of the clauic tbesis, it faill to rif,1tt tbiI tbesis.